Pengaruh Kepuasan Pelanggan dan Kualitas Layanan Terhadap Loyalitas Pelanggan pada E-Commerce Shopee - Taqdirul Alim; Zufriah, Deniyati; Muhammad Isnaini Fathoni (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2025)
This research aims to analyze the influence of customer satisfaction and service quality on customer loyalty at the e-commerce company Shopee. The research design used is quantitative research. The population of this study are active customers of the Shopee e-commerce platform in Indonesia. The sampling method used in this research was purposive sampling and used a questionnaire in data collection. Meanwhile, data analysis uses multiple regression. The research results show that customer satisfaction and service quality have a significant influence on customer loyalty, where customers who are satisfied with the quality of products and services tend to be more loyal and have the potential to make repeat purchases. The conclusion of this research is that e-commerce companies need to continue to improve customer satisfaction through improving service and product quality, as well as responsiveness to customer needs and complaints, in order to ensure sustainable customer loyalty and stable business growth.